RELATIONSHIP BETWEEN CROP DEVELOPMENTAL PHASES AND AIR TEMPERATURE AND ITS EFFECT ON YIELD OF THE WHEAT CROP (Triticum aestivum L.) GROWN IN JAVA ISLAND, INDONESIA - I. Handoko (SEAMEO BIOTROP, 2007)
About four million tonnes of wheat has been imported annually, because hardly no wheat crop is cultivated in Indonesia. High temperature is probably the major limiting factor for cultivating the crop in a large scale. This research aims to find out the relationship between temperature and wheat (DWR162 cultivar) crop development to derive its developmental parameters (base temperature and thermal unit) and to further study its effects on grain yield. Experiment was conducted at five locations in Java Island with distict altitudes range from 28 to 1,650 m to represent a wide range of averaged air temperature (27.5 to 16.5 oC). The base temperature derived from this experiment were 8.3, 3.8, and 15.1 oC while the parameters of thermal unit were 189, 1053 and 290 d. oC, respectively for the phases of sowing-emergence, emergence-anthesis, and anthesis-physiological maturity. Grain yield of the wheat crop decreased with increasing temperature of about 10% per 1oC increase above averaged temperature of 16.5 oC. Increasing temperature caused shorter duration during vegetative growth (emergence-anthesis) and grain filling period (anthesis-maturity which resulted in smaller biomass and the grain yield.